2016
DOI: 10.4274/turkderm.43403
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between uraemic pruritus and quality of life scores in hemodialysis patients

Abstract: Background and Design: Preliminary findings indicate that the adverse effects of hemodialysis (HD) impair mental, physical and social wellbeing as well as the renal disease itself. Little is known about the influence of uraemic pruritus on HD patients' well-being. We aimed to assess the association of pruritus with dermatology-specific health-related quality of life and general quality of life in HD patients. Materials and Methods: Forty-five patients with chronic renal failure, over 18 years of age, on regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Due to ESRD, uremic toxins cannot be eliminated from the body and uremic pruritus is frequently observed especially in HD patients (Kücükünal et al, 2015). Studies have reported that uremic pruritus with itching and dry skin is frequently observed in 40-90% of ESRD (Ramakrishnan et al, 2013).…”
Section: Quality Of Life In Dıalysis Treatment Optionsmentioning
confidence: 99%
“…Due to ESRD, uremic toxins cannot be eliminated from the body and uremic pruritus is frequently observed especially in HD patients (Kücükünal et al, 2015). Studies have reported that uremic pruritus with itching and dry skin is frequently observed in 40-90% of ESRD (Ramakrishnan et al, 2013).…”
Section: Quality Of Life In Dıalysis Treatment Optionsmentioning
confidence: 99%
“…Uremic pruritus can cause physical, psychosocial, and emotional deterioration in general health perceptions of patients (1,6). Uremic pruritus generally reduces the dermatological quality of life of HD patients due to the continuous sense of itching and lesions and dryness occurring due to itching (10). Uremic pruritus causes sleeplessness, fatigue/exhaustion, anger, anxiety, depression as well as decreased self-esteem, social isolation, a decline in self-care and quality of life, along with the scratching behavior during the day and especially at night, making the disease management more difficult (4)(5)(6)(7)(8)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%
“…Due to these itching-related problems, patients have a 17% higher mortality rate, along with pruritus and sleep problems, than regular HD patients (14). In a study conducted on HD patients, it was indicated that the dermatological quality of life of patients with uremic pruritus was low (4,10,15).…”
Section: Introductionmentioning
confidence: 99%
“…Küçükünal ve ark. 'nın [13] çalışmalarında diyalize giren hastaların %60'nda ÜP görüldüğünü ve bu hastaların dermatolojik yaşam kalitesinin düşük olduğunu bildirmiştir. Üremik pruritusta kaşıntıyı gidermeye yönelik semptomatik tedavi uygulanmaktadır [12].…”
Section: Introductionunclassified